Weed dynamics in crop+fish farming systems in summer fallow of double cropped lowland rice fields - Madankumar, M.; John, Jacob; Pillai, P. Shalini; Rani, B. (Journal of Tropical Agriculture, 2019)
A field study was conducted in double cropped lowland rice fields during summer of 2016 to assess the crop performance and changes in weed species and weed population in different crop (amaranth, culinary melon, fodder cowpea) + fish (catla, rohu) farming systems vis-à-vis sole cropping. Productivity of culinary melon and amaranth was higher when integrated with fish compared to the sole crop. Culinary melon+fish system recorded the highest rice equivalent yield (REY). Among the weeds, grasses dominated followed by sedges and broad leaved weeds. Among grasses, population of Echinochloa colona was the highest followed by Isachne miliacea, Digitaria ciliaris and Eragrostis tenella. Among broad leaved weeds, Lindernia grandiflora ranked first followed by Phyllanthus niruri, Oldenlandia umbellata and Cleome rutidospermum. Among sedges, Fimbristylis miliacea outnumbered others. Lower weed dry matter production and higher weed control efficiency were observed when crops were integrated with fish. Culinary melon+fish system performed better in terms of weed control and productivity.